The Effect of Vertebral Body Tethering on Spine Motion in Adolescent Idiopathic Scoliosis: A Pilot Study - Maksimovic, Mina (Université d'Ottawa / University of Ottawa, 2021)
The current gold standard for the surgical treatment of adolescent idiopathic scoliosis (AIS) is posterior spinal fusion and instrumentation (PSF); however, decreased normal spine function, strain on unfused vertebrae and pain have been suggested as long-term complications with this technique. Vertebral body tethering (VBT) is a novel and minimally invasive approach for scoliosis correction that does not involve fusion and may theoretically preserve spine motion. VBT involves the use of screws and a tether that are inserted thoracoscopically on the convexity of the spine curvature in skeletally immature patients, allowing progressive curve correction as skeletal maturity is achieved. No research to date has explored the effect of VBT on spine motion in AIS. Therefore, the purpose of this thesis was to retrospectively compare global and intersegmental spine range of motion in adolescents (9-18 years of age) without spine deformity, adolescents with untreated AIS, adolescents having undergone PSF, and adolescents having undergone VBT to gain insight on the effect of VBT on spine motion. Twenty participants were recruited into four groups including Control (n = 6), untreated AIS (n = 5), post-operative PSF (n = 4) and post-operative VBT (n = 5). Three-dimensional kinematics of the spine were collected and analyzed using an intersegmental spine model during constrained forward flexion, right-left lateral bending, and right-left axial twist movements. The PSF group displayed significantly lower spine ROM than the two non-operative groups during thoracic and total left axial twist (p ≤ 0.048), whereas thoracic and total spine range of motion during right-left lateral bending is almost equally lower in the PSF (p ≤ 0.03) and VBT (p ≤ 0.01) groups when compared to the Control and AIS groups. These results may suggest some preservation of spine motion in the transverse plane following VBT; however further investigation with a greater sample size and a prospective study design is needed to support and prove the theoretical preservation of spine motion following VBT.
Keywords: Adolescent Idiopathic Scoliosis; Spine Motion; Vertebral Body Tethering; Posterior Spinal Fusion and Instrumentation